Effects of Ostertagia ostertagi and omeprazole treatment on feed intake and gastrin-related responses in the calf - Fox, Mark T.; Uche, U. E.; Vaillant, Camille; Ganabadi, Shanti; Calam, John (Elsevier Science, 2002)
Infection with the bovine abomasal nematode, Ostertagia ostertagi, results in a loss of acid-secreting parietal cells and an increase in gastric pH. The effects of an experimental infection with Ostertagia and/or daily treatment with omeprazole (OMP) at 2 mg kg−1 bodyweight for four consecutive days (experiment days 24–27, inclusive) on voluntary feed intake, blood and tissue gastrin concentrations, abomasal G-cell numbers, gastric pH, and blood cholecystokinin (CCK) and pepsinogen concentrations were investigated in the calf. Ostertagia-infected calves demonstrated a significant drop in feed intake between days 24 and 27 post-infection (38%; P<0.001) and in G-cell numbers (42%; P<0.05) and significant increases in abomasal pH (P<0.001), fundic mucosal weight (99%; P<0.01), and blood gastrin (P<0.05) and pepsinogen (P<0.0001). OMP treatment of worm-free animals resulted in a significant drop in intake between days 24 and 27 (30%; P<0.001) and in G-cell numbers (17%; P<0.05) and significant increases in abomasal pH (P<0.01) and blood gastrin (P<0.001). OMP treatment of Ostertagia-infected animals with an existing hypergastrinaemia had no effect on feed intake, abomasal pH, blood gastrin or pepsinogen or abomasal G-cell numbers. Blood CCK concentrations were also unaffected by either Ostertagia infection or OMP treatment. These data suggest that: (a) the depression in feed intake associated with OMP in worm-free calves was not due to a side effect of drug treatment; (b) inappetance in Ostertagia-infected animals is closely associated with the parasite-induced hypergastrinaemia; and (c) the elevation in abomasal pH was a major factor responsible for the elevated blood gastrin concentrations seen in parasitised and OMP-treated animals.